Making Smart Cities More Playable. Exploring Playable Cities. - (:unkn) unknown (Springer, 2020)
This book explores the ways in which the broad range of technologies that make up the smart city infrastructure can be harnessed to incorporate more playfulness into the day-to-day activities that take place within smart cities, making them not only more efficient but also more enjoyable for the people who live and work within their confines. The book addresses various topics that will be of interest to playable cities stakeholders, including the human–computer interaction and game designer communities, computer scientists researching sensor and actuator technology in public spaces, urban designers, and (hopefully) urban policymakers.
Keywords: Smart City; Spielfläche; Spielmöglichkeit; Spielflächenplanung; Öffentlicher Raum; Straßenraum; Straßenraumgestaltung; Digitalisierung; Digitale Medien; Shared Space; Kinderspielbereich; Freiraumnutzung; Naherholungsraum; Stadtentwicklung; International